A modern vision of nursing in e-Health system - Binkowska-Bury, Monika; Nagórska, Małgorzata; Januszewicz, Paweł (Nursing Problems / Problemy Pielęgniarstwa, 2010)
In resent years, a development of modern telecommunications technologies has been used in many disciplines, including nursing as well. Advanced technologies have an incredible potential, enable to improve and simplify everyday nursing practice, save nurses’ valuable time and effectively communicate with patients. Therefore, a modern vision of nursing challenges to respond to the demand of telecommunication technologies development. This paper aims to discuss challenges of advanced telecommunication technologies in modern vision of nursing. The paper describes changes in nursing, that have occurred as a result of advanced technologies. It presents the effects that technology has had on nursing practice and therefore, identifies ways in which modern technologies could be incorporated in Polish nursing. Nursing Topics 2010; 18 (3): 342-347